2015
DOI: 10.21273/jashs.140.3.272
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of Sweetpotato Germplasm for Yield, Dry Matter Content, and Anthocyanin Production

Abstract: Interest in the potential of sweetpotato (Ipomoea batatas) for the production of industrial products is increasing. As part of an effort to evaluate the potential of sweetpotatoes for starch and anthocyanin production in the southeastern United States, a 5 × 5 North Carolina mating design II (NCII mating design) was developed to estimate the relative importance of general and specific combining abilities for dry matter (DM) content, total monomeric anthocyanin (TMA) concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The generation of so extreme hybrid genotypes (transgressive segregation) is probably due to the highly heterozygous, autotetraploid nature of cultivated potato. In spite of the lack of quantitative genetic studies in tetrasomic potato with regard to bioactive potential, similar segregation patterns were reported by Todd, Truong, Pecota, and Yencho () in a sweet potato population generated from a diallel mating scheme. As previously mentioned, the factor year was highly significant for all the studied traits.…”
Section: Discussionsupporting
confidence: 76%
“…The generation of so extreme hybrid genotypes (transgressive segregation) is probably due to the highly heterozygous, autotetraploid nature of cultivated potato. In spite of the lack of quantitative genetic studies in tetrasomic potato with regard to bioactive potential, similar segregation patterns were reported by Todd, Truong, Pecota, and Yencho () in a sweet potato population generated from a diallel mating scheme. As previously mentioned, the factor year was highly significant for all the studied traits.…”
Section: Discussionsupporting
confidence: 76%
“…HPTLC has revealed that there are five major anthocyanins, two cyanidin-based (blue bands) and three peonidin-based (red bands), but that different ratios exist. In the US, breeding lines have also been evaluated and positive correlations between yield, dry matter and total anthocyanin content were observed, indicating that improvement of major traits would be feasible with conventional breeding techniques (Todd et al, 2015). It appears that in Vanuatu, there is sufficient variation for TA improvement but that TCQAs not TAs are the major compounds contributing to the antioxidant activity of microwaved sweet potatoes.…”
Section: Variety Selection Based On Phenolic Compoundsmentioning
confidence: 99%